An annotated checklist of the birds of Manusela National Park, Seram. Birds recorded on the Operation Raleigh Expedition - John Bowler; John Taylor (KUKILA, 1989)
Manusela National Park is located in central Seram at 129 deg E, 3 deg S and covers an area of 186 000 ha, about 11% of the surface area of Seram. The Park contains a broad selection of the habitats present in Seram, stretching from the north coast to within 5 km of the south coast. It includes a large portion of the Binaia-Merkele limestone massif with the highest mountain on Seram, Gunung (G). Binaia, at 24.90m, as well as the lower parallel ridge of Gunung (G). Kobipoto (1500 m) to the north, together with a broad section of the lowland alluvial plain where three wide rivers, the Wae Toluorang, Mual and Isal drain northwards to the sea (see fig.1). Observations were made by the authors between 20 July and 25 September 1987 as part of the ornithological research work conducted under the auspices of Operation Raleigh, Seram expedition.